Transformações lineares em um curso de Licenciatura em Matemática: uma estratégia didática com uso de tecnologias digitais - Silva, Eliza Souza da (2015)
This research has as object of study the learning of linear transformations by undergraduates in mathematics and was held having as subjects eight students in a class of second year of the Licentiateship Degree in Mathematics from the State University of Pará. The theoretical framework of the investigation rests on the theory of didactic situations, used in order to produce a didactic sequence to investigate how Mathematics Degree students are able to solve conceptual problems related to the topic "linear transformations" in the context of didactic situations using digital technologies. The employed activities are based on a didactic situation architected in order to give to subjects conditions to develop, with autonomy, their own strategies, counting with the computer program GeoGebra 5 as mediating element. The theoretical review pointed to the existence of difficulties on the part of college students in learning linear algebra contents, which were confirmed in this study. The research results showed also that the development of activities based on the conceptual framework presented through a didactic sequence properly planned and with mediation by digital technologies can help students develop autonomy in learning and considerable cognitive gains, despite remaining difficulties related to the conceptual construction